The day the crayons came home - Daywalt, Drew.; Jeffers, Oliver; Daywalt, Drew. (New York, NY : Philomel Books, an imprint of Penguin Group (USA), 2015)
One day, Duncan is happily coloring with his crayons when a stack of postcards arrives in the mail from his former crayons, each of which has run away or been left behind, and all of which want to come home.
Companion book to: The day the crayons quit.
Booklist starred
Pub Weekly
School Library Journal starred
Booklist starred, August 2015
Kirkus Review, July 2015
Keywords: Color -- Juvenile fiction; Crayons -- Juvenile fiction; Postcards -- Juvenile fiction; Color -- Fiction; Crayons -- Fiction; Postcards -- Fiction; Color -- Fiction; Crayons -- Fiction; JUVENILE FICTION / Concepts / Colors; JUVENILE FICTION / General; JUVENILE FICTION / Humorous Stories; Postcards -- Fiction